Fighting Alzheimer’s with Movement: The Role of Physical Activity in Disease Management - Agnieszka Kosińska; Magdalena Balwierz; Karolina Kalinowska; Urszula Świrk; Jan Karczmarz; Joanna Orzechowska; Marika Gutowska; Michał Orzechowski; Aleksandra Paprocka; Paulina Fijałek (Quality in Sport)
Introduction and purpose